b)\(\sqrt{4x-20}+\sqrt{x+5}-\dfrac{1}{3}\sqrt{9x-45}=4\)
c) \(\sqrt{\dfrac{3x-2}{x+1}}=3\)
d) \(\dfrac{\sqrt{5x-4}}{\sqrt{x+2}}=2\)
giải phương trình:
a) \(\sqrt{4x^2+4x+3}=8\)
b) \(\sqrt{5x^3+5x^2+7}=9\)
c) \(\dfrac{3}{5}\sqrt{x^5+4x^3+2x^2}=18\)
Tìm giá trị của x:
\(\sqrt{5x-1}-\sqrt{x+2}=\dfrac{4x-3}{5}\)
GIẢI PHƯƠNG TRÌNH
a) \(\dfrac{1}{3}\sqrt{x-2}-\dfrac{2}{3}\sqrt{9x-18}+6\sqrt{\dfrac{x-2}{81}}=-4\)
b) \(\sqrt{9x^2+12x+4}=4x\)
c) \(\sqrt{9x-18}-\sqrt{4x-8}+3\sqrt{x-2}=40\)
d) \(\sqrt{5x-6}-3=0\)
1\(\sqrt{5+2\sqrt{8}}-\sqrt{5-2\sqrt{8}}\) 2)\(\dfrac{\sqrt{x^2+2\sqrt{3x}+3}}{x^2-3}\) 3) \(\dfrac{\sqrt{x^2-5x+6}}{\sqrt{x-2}}\) 4)\(\dfrac{\sqrt{\left(x-4\right)^2}}{x^2-5x+4}\) 5) \(\dfrac{3x+1}{\sqrt{9x^2+6x+1}}\)
a) \(\sqrt{4x^2-9}=2\sqrt{x+3}\)
b) \(\sqrt{4x+20}+3\sqrt{\dfrac{x-5}{9}}-\dfrac{1}{3}\sqrt{9x-45}=4\)
c) \(\dfrac{2}{3}\sqrt{9x-9}-\dfrac{1}{4}\sqrt{16x-16}+27\sqrt{\dfrac{x-1}{81}}=4\)
d)\(5\sqrt{\dfrac{9x-27}{25}}-7\sqrt{\dfrac{4x-12}{9}}-7\sqrt{x^2-9}+18\sqrt{\dfrac{9x^2-81}{81}}=0\)
d) \(x-5\sqrt{x}+6=0\)
e) \(\sqrt{x-1}+\dfrac{3}{2}\sqrt{4x-4}-\dfrac{2}{5}\sqrt{25x-25}=4\)
f) \(\sqrt{x-5}+\sqrt{4x-20}-\dfrac{1}{3}\sqrt{9x-45}=6\)
a)\(\sqrt{4-5x}=12\) tìm x
b)\(\sqrt{10+\sqrt{3x}}=2+\sqrt{6}\)
c)\(\sqrt{4x+20}-3\sqrt{5+x}+\dfrac{4}{3}\sqrt{9x+45}=6\)
Giải phương trình:
a) \(\sqrt{x+3}+\dfrac{4x}{\sqrt{x+3}}=4\sqrt{x}\)
b \(2x^4-5x^3+6x^2-5x+2=0\)